2008
DOI: 10.2147/vhrm.s3467
|View full text |Cite
|
Sign up to set email alerts
|

Update on the use of Trandolapril in the management of cardiovascular disorders

Abstract: Abstract:Trandolapril is a well known angiotensin converting enzyme (ACE) inhibitor with many cardiovascular (CV) indications. The objectives of this article are to review the pharmacokinetics and pharmacodynamics properties of trandolapril and to focus on its clinical relevance in cardiovascular medicine. Various populations have been studied in large clinical trials including patients with congestive heart failure (CHF) after an acute myocardial infarction (AMI), diabetics, patients with hypertension (HTN), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
1
1
0
Order By: Relevance
“…due to myocardial infarction, trandolapril decreased the mortality rate, incidence of atrial fibrillation, risk of sudden death, and development of severe heart failure (Diaz and Ducharme, 2008). Similar to clinical studies, multiple vascular and cardiac effects of trandolapril were also demonstrated in animal models (Fornes et al, 1992;Koffi et al, 1998;Tanonaka et al, 2001).…”
Section: Discussionsupporting
confidence: 58%
“…due to myocardial infarction, trandolapril decreased the mortality rate, incidence of atrial fibrillation, risk of sudden death, and development of severe heart failure (Diaz and Ducharme, 2008). Similar to clinical studies, multiple vascular and cardiac effects of trandolapril were also demonstrated in animal models (Fornes et al, 1992;Koffi et al, 1998;Tanonaka et al, 2001).…”
Section: Discussionsupporting
confidence: 58%
“…Since decreasing blood pressure is vital in lowering the risk of developing cardiovascular problems in patients with type 2 diabetes mellitus, a combination of anti-diabetic and anti-hypertension drugs is required and widely employed (Sharma et al, 2007). In vitro and clinical research studies have shown that verapamil inhibits P-gp (Nies et al, 2011;Uchida et al, 2014).…”
Section: Introductionmentioning
confidence: 99%